A STUDY OF CURRENT EVENTS AND IMPLEMENTATION: LA POLAR S.A FINANCIAL SCANDAL AND ITS ECONOMIC CONTRAST BY THE FINANCIAL MASS METHOD - Alejandro Torres Mussatto; Eric Salinas Mayne (European Scientific Journal, ESJ, 2014)
This work aims to deliver a professional and ethical reflection of the social responsibility of any for-profit organization under free competition and healthy economic growth and development of any given country. This is extremely important considering there is always a social responsibility with the market and, above all, with the people. We consider that an ethical crisis ends up creating a financial crisis motivated by bad practices. Thus, we will study this kind of practice carried out by the managers of La Polar S.A. in Chile. With publicly available information, mainly consolidated financial statements, we are able to apply a new so-called financial analysis method, "financial mass", in which homogeneous monetary aggregates enable to classify the accounting information. This proposal interprets financial statements, specifically those indexes derived from it, and compares them to traditional indexes. This will allow us to conclude that the company under study showed figures much higher than in the industrial sector. Therefore, with the publicly available information, it is possible to notice the irregularity that would later on impact the Chilean capital market .